KONTEKSTUALISASI PENAFSIRAN QS AL-NUR [24]; 31 (APLIKASI HERMENEUTIKA MA’NA CUM MAGHZA) - M. Hendrik Pratama (IAIN Madura, 2022)
A verse of the Qur’an commends the covering of aurat to maintain honor for women is stated in QS al-Nur [24]: 31. However, there is a distortion of the main message which contradicts the verse with the emerging phenomena of jilboobs among women both teenagers and adults. The approach used in this study was qualitative with a literature review method. The hermeneutical approach of ma'na cum maghza was employed to interpret QS al-Nur [24]: 31. The study revealed that the historical significance of this verse is the ethics of socializing for women in its socio-cultural sphere. In addition, the verse QS. al-Nur [24]: 31 is also a proposition that prohibits the phenomenon of jilboobs. Meanwhile, its dynamic significance, first, not to see photo and watch video uploads of aurat expose as a ghadd al-bashr practice. Second, not commiting immorality by avoiding virtual sex such as sex video calls. Third, QS al-Nur [24]: 31 is also the basis for the prohibition of flexing behavior and the exhibition of personal property and wealth in the social media and social media.